Health-promoting domains and lifestyle of a sample of Brazilian adolescents - Dartagnan Pinto Guedes; Marizete Arenhart Zuppa; Bruna Hatsue Santos Yamaji (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Reports indicate that the health habits of adults are strongly linked to the behaviors incorporated in adolescence. Therefore, it is essential to monitor the lifestyle of adolescents to promote their present and future health. This study aimed to identify differences in health-promoting domains according to demographic data and lifestyle behaviors, including physical activity, sedentary behavior, sleep duration, and food intake, in a sample of Brazilian adolescents. MATERIALS AND METHODS: Cross-sectional school-based study, with the participation of 306 adolescents aged 14 to 18 years. A questionnaire was applied with structured questions to collect demographic data and lifestyle behaviors. To examine the health-promoting domains the Adolescent Health Promotion Scale (AHPS) was used. Data were analyzed using multivariate analysis. RESULTS: Scores attributed to each of the health-promoting domains showed substantial variations according to sex, age, year of study, parents' schooling, and family economic class. After adjustment for covariables, the adolescent who presented significantly higher scores equivalent to the overall index of health promotion reported being more physically active (F = 4.848; P = 0.009), sleeping 6-8 hours/night (F = 2.328; P = 0.046), consuming fruit/vegetable more frequently (F = 3.168; P = 0.024), while sedentary behavior and intake of sweetened products/soft drinks have not shown any significant effect. CONCLUSION: The findings confirmed the consistent positive influence of health-promoting domains assessed by AHPS on healthy lifestyle behaviors, suggesting in the intervention programs aimed at adopting healthy lifestyle approaches it is important enough to contemplate actions aimed at all the areas of health promotion with characteristics aimed at nutrition behavior, social support, health responsibility, life appreciation, exercise behavior, and stress management.